High-Quality Epitaxial N Doped Graphene on SiC with Tunable Interfacial Interactions via Electron/Ion Bridges for Stable Lithium-Ion Storage - Sun, Changlong; Xu, Xin; Gui, Cenlin; Chen, Fuzhou; Wang, Yian; Chen, Shengzhou; Shao, Minhua; Wang, Jiahai (Nano-Micro Letters, 2023)
Tailoring the interfacial interaction in SiC-based anode materials is crucial to the accomplishment of higher energy capacities and longer cycle lives for lithium-ion storage. In this paper, atomic-scale tunable interfacial interaction is achieved by epitaxial growth of high-quality N doped graphene (NG) on SiC (NG@SiC). This well-designed NG@SiC heterojunction demonstrates an intrinsic electric field with intensive interfacial interaction, making it an ideal prototype to thoroughly understand the configurations of electron/ion bridges and the mechanisms of interatomic electron migration. Both density functional theory (DFT) analysis and electrochemical kinetic analysis reveal that these intriguing electron/ion bridges can control and tailor the interfacial interaction via the interfacial coupled chemical bonds, enhancing the interfacial charge transfer kinetics and preventing pulverization/aggregation. As a proof-of-concept study, this well-designed NG@SiC anode shows good reversible capacity (1197.5 mAh g−1 after 200 cycles at 0.1 A g−1) and cycling durability with 76.6% capacity retention at 447.8 mAh g−1 after 1000 cycles at 10.0 A g−1. As expected, the lithium-ion full cell (LiFePO4/C//NG@SiC) shows superior rate capability and cycling stability. This interfacial interaction tailoring strategy via epitaxial growth method provides new opportunities for traditional SiC-based anodes to achieve high-performance lithium-ion storage and beyond. Highlights: 1 The intimate NG@SiC heterostructure has been constructed via a direct thermal decomposition method. 2 The NG@SiC heterostructure anode delivers enhanced capacity and cycling stability both in the half-cell and in the full cell. 3 DFT analysis reveals that this NG@SiC anode possesses lower lithium-ion adsorption energy and higher charge and discharge rates.